A discricionariedade do delegado de polícia na condução do inquérito policial como busca da garantia da dignidade da pessoa humana no Brasil - Prates Junior, Ulisses (2017)
The growing attention which is given to public safety nowadays takes into a deep discussion related to the study of Chief of Police´s role, who is the first actor of criminal prosecution to take the initial steps that will lead to solving a crime and that, in most of times your decision is permeated of discretionary, space that reveals the importance of his ethics skills for taking decisions that must always preserve human dignity